IS THE FUTURE HYBRID? AN ANALYSIS OF OPPORTUNITIES FOR DIGITAL EDUCATION - BRETAN, Bianca Doris (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Is the Future Hybrid? An Analysis of Opportunities for Digital Education. The year 2020 undoubtedly marked a turning point in education. The abrupt passage to online teaching created an overwhelming feeling of uncertainty regarding the aims, efficiency, and outcome of this type of educational endeavor. Nevertheless, the two years with strict anti-epidemic measures and frustrating lockdowns have opened an opportunity to rethink the in-person traditional teaching experience. The current article wants to analyze the main concepts that provide the framework for online teaching and to answer the following research question: Are post pandemic undergraduate students more willing to use online learning? The research method is based on responses to a questionnaire survey sent to students in one subject area: legal studies. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is then used to provide a framework to better understand the present and future situation of online education. The conclusion suggests that the recent online teaching experience changed students’ perception on digital pedagogy, indicating a new direction to all educators. Article history: Received 31 July 2022; Revised 15 October 2022; Accepted 4 November 2022; Available online 20 December 2022; Available print 30 December 2022. REZUMAT. Va fi viitorul hibrid? O analiză de oportunități in educația digitală. Anul 2020 a marcat un punct de cotitură in educație. Trecerea abruptă la învățarea online a creat un sentiment generalizat de incertitudine în ceea ce privește obiectivele, eficiența și finalitatea demersului didactic de acest tip. Cu toate acestea, cei doi ani presărați cu măsuri anti-epidemice stricte și restricții frustrante au deschis perspectiva regândirii pedagogiei clasice. Articolul de față își propune să analizeze principalele concepte care au contribuit la modelarea unui cadru pentru învățarea online și să răspundă următoarei întrebări: Sunt studenții generației post-pandemie mai deschiși spre învățarea online? Metodologia utilizată implică folosirea unui chestionar adresat unui grup de studenți în primul an de studiu la Facultatea de Drept. În urma analizării datelor și validarea întrebării propuse a fost utilizată analiza de tip SWOT. Cuvinte-cheie: educație hibridă, pandemie, competențe digitale, învățare online, analiză SWOT